UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DENGAN METODE IMPROVE - Arifatul Umamah (Pendidikan Matematika | STKIP YM Bangko, 2019)
This study aims to describe the increase in students' understanding of mathematical concepts by using the improve method in class IX B students at SMP Negeri 17 Merangin in the 2015/2016 Academic Year. The research method is classroom action research. Data collection techniques using observation, interviews, documentation, and test the description of the ability to understand concepts. Data analysis techniques using analysis of student activity observations. Based on the results of the study obtained a percentage of student activity 52% in the first cycle and 60.5% in the second cycle or an increase of 8.5%. While the concept comprehension ability test was obtained an average of 69.46 in the first cycle and 80.00 in the second cycle or an increase of 10.54. So it can be concluded that by applying the improve method can improve the ability to understand the concepts of class IX B students of SMP Negeri 17 Merangin in the 2015/2016 academic year.